The effects of informal land markets on urban land development in rapidly growing urban areas: the case of Sululta town, Ethiopia - Abebe, Birhanu Girma; Dadi, Birhanu Uma; Bifa, Adane Obsie (Frontiers in Sustainable Cities, 2024)
The informal land market presents a significant challenge to urban land development in many developing countries, including Ethiopia. For example, in cities adjacent to Addis Ababa, rapid horizontal expansion accompanied by various land development issues is a common phenomenon. The study was conducted to examine the effects of the informal land market in Sululta town. Parameters such as the rate of urban expansion, settlement density, level of consumption of the natural environment, and land suitability were used to investigate these problems further. Geographic Information System (GIS), trend analysis models, and overlay analysis, supported by relevant literature reviews, were employed to address the research questions. The study’s findings indicate that Sululta is characterized by low-density urban expansion, significant ecological degradation, and rapid horizontal sprawl. It is recommended that the local government implement an effective land policy to meet the increasing land demand, establish a robust formal land market system, and apply predevelopment urban planning strategies.